Elucidating the metabolic characteristics of pancreatic β-cells from patients with type 2 diabetes (T2D) using a genome-scale metabolic modeling. (May 2022) - Paul, Abhijit; Azhar, Salman; Das, Phonindra Nath; Bairagi, Nandadulal; Chatterjee, Samrat
Abstract: Diabetes is a global health problem caused primarily by the inability of pancreatic β-cells to secrete adequate insulin. Despite extensive research, the identity of factors contributing to the dysregulated metabolism-secretion coupling in the β-cells remains elusive. The present study attempts to capture some of these factors responsible for the impaired β-cell metabolism-secretion coupling that contributes to diabetes pathogenesis. The metabolic-flux profiles of pancreatic β-cells were predicted using genome-scale metabolic modeling for ten diabetic patients and ten control subjects. Analysis of these flux states shows reduction in the mitochondrial fatty acid oxidation and mitochondrial oxidative phosphorylation pathways, that leads to decreased insulin secretion in diabetes. We also observed elevated reactive oxygen species (ROS) generation through peroxisomal fatty acid β-oxidation. In addition, cellular antioxidant defense systems were found to be attenuated in diabetes. Our analysis also uncovered the possible changes in the plasma metabolites in diabetes due to the β-cells failure. These efforts subsequently led to the identification of seven metabolites associated with cardiovascular disease (CVD) pathogenesis, thus establishing its link as a secondary complication of diabetes. Highlights: Genome-scale metabolic model built to provide insights into β-cell metabolism in T2D patients. Co-expression network analysis reveals that most dysregulated metabolic genes form a cluster. ATP production is affected due to the reduced mitochondrial fatty acid oxidation and oxidative phosphorylation. ROS generation increases through peroxisomal fatty acid β-oxidation, and cellular antioxidant defense systems get hampered. Identified seven metabolites secreted by β-cell that are associated with cardiovascular disease pathogenesis.